Islamic Religious Education Strategies for Enhancing Student Motivation: A Synthesis of Research Findings - Syatria Adymas Pranajaya; Randi Muhammad Gumilang; Dedi Wahyudi; Agus Wahyudi (Education Studies and Teaching Journal (EDUTECH), 2024)
This study is a systematic literature review that aims to investigate various Islamic religious education strategies and the diverse motivational needs of students. Through analysis of existing literature, this study highlights the importance of integrating traditional Islamic teachings with contemporary educational methods to foster holistic development and moral values ​​among students. This research method involves searching and analyzing various related scientific articles indexed in the Scopus Q1 database. Research findings show that adapting Islamic religious education strategies is key in meeting the diverse motivational needs of students. The implications of this research emphasize the importance of developing inclusive and diverse educational approaches, as well as supporting effective and meaningful learning for all students in the context of Islamic religious education.